Submission to the Marine Farming Planning Review Panel Independent Assessment of salmon farming at Okehampton Bay - Catriona MacLeod; Donald Ross; Christopher Carter; Caleb Gardner; Neville Barrett; Gustaaf Hallegraeff; Christopher Bolch; Mary-Anne Lea (2016)
This submission has been prepared by the University of Tasmania’s Institute for Marine and Antarctic Studies (IMAS) in response to a request from the Marine Farming Planning Review Panel (the Panel) for information to address the following Terms of Reference: (a) The environmental science supporting the proposed environmental monitoring and management of salmon farming at Okehampton Bay within the Great Oyster Bay and Mercury Passage Marine Farming Development Plan 1998 (as reviewed in 2007) area: (b) The adequacy of the environmental baseline data and surveys to allow the Director, Environmental Protection Authority to establish a contemporary environmental management regime for the purposed marine farming activity: (c) The adequacy of the Great Oyster Bay and Mercury Passage Marine Farming Development Plan October 1998 to allow for the implementation of a contemporary environmental management regime for proposed salmonid marine farming at Okehampton Bay: We hope that this submission provides the Panel with an understanding of the research that has been undertaken by IMAS and its predecessors, commonly and in collaboration with other organisations, to inform both management and monitoring of salmon farming in Tasmania as a whole as well as UTAS/ IMAS research information and knowledge specifically relevant to the environmental management of salmon farming in Okehampton Bay specifically.